A role for HLA‐DRB1*1101 and DRB1*0801 in cognitive ability and its decline with age. Issue 2 (16th October 2015) - Payton, Antony; Dawes, Piers; Platt, Hazel; Morton, Cynthia C.; Moore, David R.; Massey, Jonathan; Horan, Michael; Ollier, William; Munro, Kevin J.; Pendleton, Neil
Abstract : Cognitive abilities (memory, processing speed, vocabulary, and fluid intelligence) are correlated with educational attainment and occupational status, as well as physical and mental health. The variation in cognitive abilities observed within a population has a substantial genetic contribution (heritability ∼50%) and yet the identification of genetic polymorphisms from both genome‐wide association and candidate studies have to date only uncovered a limited number of genetic variants that exert small genetic effects. Here we impute human leukocyte antigens (HLA) using existing genome‐wide association data from 1, 559 non‐pathological elderly volunteers who have been followed for changes in cognitive functioning between a 12‐ and 18‐year period. Specifically, we investigate DRB1*05 (*11/*12) and DRB1*01, which have previously been associated with cognitive ability. We also analyze DRB1*0801, which shares close sequence homology with DRB1*1101. Together with DRB1*1101, DRB1*0801 has been associated with several diseases including multiple sclerosis and primary biliary cirrhosis, which themselves are associated with cognitive impairment. We observed that both DRB1*0801 and DRB1*1101 were significantly associated with vocabulary ability (cross‐sectional and longitudinal scores) and that the effects were in opposite directions with DRB1*0801 associated with lower score and faster decline. This opposing affect is similar to that reported by other groups in systemic lupus erythematosus, type 1 diabetes, and primary biliary cirrhosis. DRB1*0801 was also significantly associated with reduced memory ability. We observed no associations between cognitive abilities and DRB1*01 or DRB1*12. © 2015 Wiley Periodicals, Inc.